1996
DOI: 10.1136/emj.13.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Children with seizures presenting to accident and emergency.

Abstract: Abstractwith seizures. Children presenting with Objective-To analyse the diagnoses made seizures have a potentially broad range of in children presenting to an accident associated problems that require appropriate and emergency (A&E) department with management. Such an analysis would be useful seizures.for planning district A&E and paediatric Methods-All children who presented to a services. district general hospital A&E department with seizures over a 1 year period were Methods identified. A retrospective rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
40
3
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 20 publications
8
40
3
1
Order By: Relevance
“…Previous studies reported that seizures accounted for approximately 1-2% of all pediatric emergency department visits. [7][8][9][10][11] In our study, only 0.28% of all emergency department visits were due to a convulsive epileptic seizure. The very low incidence of seizures among all pediatric emergency department visits may be due to the fact that emergency departments in Turkey have become a common place for both urgent and non-urgent child healthcare provision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that seizures accounted for approximately 1-2% of all pediatric emergency department visits. [7][8][9][10][11] In our study, only 0.28% of all emergency department visits were due to a convulsive epileptic seizure. The very low incidence of seizures among all pediatric emergency department visits may be due to the fact that emergency departments in Turkey have become a common place for both urgent and non-urgent child healthcare provision.…”
Section: Discussionmentioning
confidence: 99%
“…10 In another study, 5% of all children who presented with a seizure were diagnosed with status epilepticus. 9 Although the majority of the seizures stopped before arrival to the emergency department, it was imperative to administer the appropriate anti-convulsant medication and arrange intensive care referral in case of status epilepticus.…”
Section: Discussionmentioning
confidence: 99%
“…In many children, the history and physical examination alone will provide adequate information regarding probable cause of the seizure 12 or the need for other tests including neuroimaging. 13 The etiology of the seizure may necessitate prompt treatment or provide important prognostic information.…”
mentioning
confidence: 99%
“…Although, it is commonly agreed that outcome is primarily a function of underlying aetiology, there is still much controversy as to which other factors such as age, duration, treatment or CSE itself, modify the outcome [12,21,23,24]. Where there has been no acute or progressive central nervous system insult, morbidity and mortality are low [4,5,17,20,[25][26][27]. Failure to diagnose and treat status epilepticus in a prompt and accurate manner has been shown to result in significant overall mortality and neurological morbidity [17,23,28].…”
Section: Introductionmentioning
confidence: 99%
“…Status epilepticus in childhood is a life threatening condition with serious risk of neurological sequelae and constitutes a medical emergency [2,4,5]. According to the Canadian Paediatric society the commonest cause of status epilepticus is prolonged febrile convulsion [6].…”
Section: Introductionmentioning
confidence: 99%